Educação e diversidade sexual: a (in) visibilidade nos planos de ensino da área de ciências humanas e suas tecnologias no ensino médio maranhense - MARTINS, Alberto Magno Moreira (2016)
This research sought to examine the issue of approach to sexual diversity, specifically homosexuality, in the "Human Sciences and their Technologies" Middle Public State of Maranhão Network Education, with the locus of the research school of high school Maranhense where analyzed the Pedagogical political Project and Plans of Humanities Education Area and its focus on technology in curriculum components: Sociology, Philosophy, History and geography. In the methodological approach, we chose the qualitative analysis through desk research, based on content analysis, using the recording unit based on the reality of a reference school in St. Louis, which allowed the issue of scrolling with approaches about sexual diversity and inclusion, respect and appreciation of diversity, educational policies in Brazil and Maranhão and research analysis on the spot through the incursion in the Pedagogical political Project and the Teaching Plans Human Sciences Area and its technologies. In this context, we consider that the issue analyzed is little discussed in all approaches, which we consider a contradiction when all public policies and school on their instruments speak of democratic education and social inclusion, as these present silencing and at times omissions about sexual diversity, sexual orientation, gender and inclusion.